2015
DOI: 10.1017/s1041610215001350
|View full text |Cite
|
Sign up to set email alerts
|

PerCEN trial participant perspectives on the implementation and outcomes of person-centered dementia care and environments

Abstract: Successful knowledge translation of the person-centered model starts with managerial leadership and support; it is sustained when staff are educated and assisted to apply the model, and, along with families, come to appreciate the benefits of flexible care services and teamwork in achieving resident well-being. The Australian New Zealand Clinical Trials Registry number is ACTRN 12608000095369.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(127 citation statements)
references
References 17 publications
(30 reference statements)
6
121
0
Order By: Relevance
“…Given these considerations and the variety of methodologies and perspectives of the qualitative studies included, a domains-based approach was used to examine quality. To illustrate the variety of qualitative studies included: one study used a phenomenological action research approach (Lykkeslet, Gjengedal, Skrondal, & Storjord, 2014) others used content analysis or videotaped interaction-data (Chenoweth et al, 2015;Hammar, Emami, Engstrom, & Gotell, 2011;Lykkeslet et al, 2014;Soderlund, Cronqvist, Norberg, Ternestedt, & Hansebo, 2013); one study focused on organisational acceptability of the training rather than on participant experience (Chenoweth et al, 2015).…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Given these considerations and the variety of methodologies and perspectives of the qualitative studies included, a domains-based approach was used to examine quality. To illustrate the variety of qualitative studies included: one study used a phenomenological action research approach (Lykkeslet, Gjengedal, Skrondal, & Storjord, 2014) others used content analysis or videotaped interaction-data (Chenoweth et al, 2015;Hammar, Emami, Engstrom, & Gotell, 2011;Lykkeslet et al, 2014;Soderlund, Cronqvist, Norberg, Ternestedt, & Hansebo, 2013); one study focused on organisational acceptability of the training rather than on participant experience (Chenoweth et al, 2015).…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 99%
“…However, others studies (e.g. Chenoweth et al, 2015;Haberstroh et al, 2011) explicitly included a Table 3. Quality assessment of qualitative studies.…”
Section: Conceptual Basismentioning
confidence: 99%
See 2 more Smart Citations
“…These studies concluded that to reach optimal effect of DCM, the implementation requires strong and accurate attention (Brownie & Nancarrow, 2013;Chenoweth et al, 2015;Dichter et al, 2015;Jaycock et al, 2006;Jeon et al, 2012;Quasdorf et al, 2017;Rokstad, Vatne, Engedal, & Selbaek, 2015;Van de Ven, 2014). Increasing the number of realized preconditions is likely to increase the success of the implementation (Chenoweth et al, 2015;Rokstad et al, 2015;Van de Ven et al, 2013). However, as DCM is a multi-component method for application in practice, realizing all preconditions is hard to accomplish.…”
Section: Discussionmentioning
confidence: 99%